Atoms of mind the "ghost in the machine" materializes - Klemm, W.R. (William Robert) 1934-; SpringerLink (Online service). (Dordrecht, Netherlands Springer, 2011)
There are books on the brain and books on the mind. However, only occasionally one finds a scholarly written thesis that explains how brain circuits give rise to perceptions, thoughts and consciousness. Bill Klemm's book belongs to this exceptional category. Using lucidly explained examples, he takes the ready on a cheerful journey from the computational elements of circuits to large-scale interactions of neuronal networks illustrating how such dynamics can support memories, decision making, perceptual binding and the conscious thought. A highly recommended reading.Atoms of Mind is an excellent, far reaching, and well-written discussion of brain-mind relationships, including brain physiology, dreams, free will, personal responsibility, and possible origins of subconscious and conscious processes in neural firing patterns. "Bill Klemm's book provides a wonderful and incredibly insightful overview for the most exciting topics in modern neuroscience, ranging from its philosophical foundations to the latest ground-breaking discoveries. Anyone wanting to have a global understanding of human minds must read it."
1. The Quest -- 2. Thinking About Thinking -- 3. Kinds of Mind -- 4. Carriers and Repositories of Thought -- 5. Specific Thought Mechanisms & Examples -- 6. Global Interactions -- 7. On the Nature of Consciousness -- 8. Theories of Consciousness -- 9. Conclusions.
Electronic reproduction.
Keywords: Brain; Neurosciences; Thought and thinking; Consciousness; Neurosciences; Neurology; Life Sciences; aNeurobiology; Electronic books